The Role of the Police in Overcoming Motorcycle Racing Actions that Disturb Road Users - Afriyanto Afriyanto; Riswadi Riswadi; Ahmad Redi (Publikasiku, 2023)
Efforts to eradicate the act of illegal racing on the road seemed endless. The police seem to be tireless in conducting raids on illegal races and they are also constantly making efforts to develop them. All methods have been tried, from the soft method to the rather hard approach. However, all the efforts and hard work of the authorities to eradicate the illegal races seemed meaningless. But the action of motor racing on the streets is still getting worse. In terms of efforts to overcome illegal racing behaviour which is very troubling to the community, law enforcement officers in this case the traffic police take preventive and repressive measures in tackling illegal racing actions. The implementation of law enforcement, especially the police, is obliged to maintain public order in order to create security and comfort in traffic. And providing a sense of security to every motorized vehicle driver, law enforcement is carried out by means of repressive efforts, which is an effort to combat illegal racing actions conceptually which was taken after the occurrence of the Illegal Racing Action. The sanction given is detention in accordance with Law No. 22 of 2009 and given a penalty in accordance with article 309, the sanction is a fine of Rp. 3,000,000.00, for a deterrent effect the police will hold the vehicle for 2 months. Countermeasures with repressive efforts are intended to take action against the perpetrators of crimes in accordance with their actions and improve them again so that they are aware that their actions are unlawful and detrimental to society